Interações interpessoais e qualidade de vida no trabalho: contribuições para a gestão organizacional - (:unkn) unknown (Universidade Federal de Goiás, 2015)
The nature of interpersonal interactions happen in the labor context and the quality of life at work (QLW) are relevant topics to the study of organizations, considering they are variables that impact, directly or indirectly, in organizational management processes, the end result of work and the dynamics of the organization. Therefore, this study investigated the interpersonal relationship patterns constructed between co-workers and the QLW of workers, through the instruments Check List of Interpersonal Transactions-II (CLOIT-II) and Assessment Scale the Quality of Life at Work (Scale -QLW). Two studies were carried out, both with employees of different areas, most residents being in the state of Goiás. In Study I, it was carried out an assessment of CLOIT-II internal structure, as it maps the interpersonal relationships of persons targeted. It was found that the checklist is set to the model on which it is founded, the circumplex model, through Multidimensional Scaling confirmatory technique. The data obtained demonstrated good measure of the adjustment indicators to a two-dimensional organization, other indicators of satisfactory circularity, however, not all psychometric criteria were satisfied circumplexidade, suggesting that CLOIT-II fits the quasi-circumplex model. In the second study, which linked the two constructs through the use of Pearson's correlation coefficient, we observed that interpersonal positions varied according to the degree of QVT, demonstrating that subjects who are more satisfied with their work, present most appropriate interpersonal interaction patterns. Both studies showed positive results, regard to a better understanding of the constructs studied, the interpersonal relationships in the workplace and the QLW, bringing contributions to the area, especially for Goiás organizations.
Interpersonal interactions and quality of life at work: contributions to organizational management
Keywords: Gestão organizacional; Relações interpessoais; Qualidade de vida no trabalho; Organizational management; Interpersonal relationships; Quality of work life; ADMINISTRACAO PUBLICA::ADMINISTRACAO DE PESSOAL